Intelligent fire detection system using mobile wireless network (2010)
To protect lives and valuables against colossal loss due to fire outbreak in any society, provision of proper safty measures is sine qua non. This has been achieved through installation of adequate fire extinquisher in strategic visible places, installation of smoke sensors and provision of human security personnel.These methods are not only cost prohibitive, but most times fail to provide required hazard preventive measures at appropraite time. In this paper, we present an intelligent photoelectric fire detection system to provide prompt and adequate notification mechanisms to the occupants and relevant authorities about possible outbreak of fire via existing mobile wireless networks. The result from the implemented model shows how intelligent photoelectric fire detection system can help minimize possible consequences from the risk of fire outbreak.